Financial Technology (Fin Tech) Credit Volume and its Implication on Women Cassava Farmers’ Profit in Anambra State (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Access to microcredit by women farmers is challenged by lack of collateral security among others. This impacts negatively on the productivity and profitability of women cassava farmers. Thus, this study examined access to financial technology (fin-tech) credit volume and its implication on profit of women cassava farmers in Anambra State. A Three-stage sampling method was adopted. Five Local Government Areas (LGA) were purposively selected. Three villages were then randomly selected from each LGA, and random sampling was used to select ten 10 women cassava farmers. In all, 150 were sampled using structured questionnaires. Data collected were access to fintech credit and profit of farmers. Data were analyzed using descriptive statistics and Ordinary Least Square. Result showed that only (36.10) had access to credit through fin-tech. Majority (47.16%) of the farmers, had access to between 5,000-30,000 Naira, (22.64%) had access to credit range of 31,000-60,000 Naira, (20.75%) had access to between 61,000-100,000 Naira while (9.43%) had access to credit worth 100,000 Naira and above. Farm size, volume of loan accessed through fintech and cost of weeding had positive and significant influence on profit, while cost of transportation had negative and significant influence on profit. The profitability of women cassava farmers was established increased with an increase in the volume of credit access through fintech. The study recommends that farmers’ access to fintech credit be improved through sensitization and provision of required resources.
Keywords: Credit volume; Financial technology; Profit; Women cassava farmers